IMPORTANCE OF GREEN ECONOMY AND INSTRUMENTS OF GREEN FINANCE IN SUSTAINABLE ECONOMIC GROWTH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article analyze current situation of green financing in Uzbekistan and how functions there are to achieve sustainable economic growth. All of main problems are discussed and given solutions with real cases.Keywords: green economy, green financing, sustainable economic growth, socio-economic development, IPO, green bonds.Introduction. In recent years, comprehensive reforms aimed at deepening structural changes, modernization and diversification of the basic sectors and directions of the country's national economy, and uniform socio-economic development of regions have been implemented in Uzbekistan. On October 5, 2019, the decision of the President of the Republic of Uzbekistan No. PQ-4477 on approving the strategy of the transition to the "green" economy of the Republic of Uzbekistan for the period of 2019-2030 came into force. In addition, the European and CIS countries aimed at fundamentally improving the legal framework and policy on "green" economy and financing in the capital city of Tashkent, and supporting innovative "green" investments through partnership relations between the state and the private sector. a conference of regional ministries on "green" economy was held.